E-033 Endovascular internal trapping as the first-line treatment for ruptured vertebral artery dissecting aneurysms. (22nd July 2018) - Raper, D; Ding, D; Savage, J; Liu, J; Caldwell, J; Brew, S; McGuinness, B
Abstract : Background: The roles of endovascular internal trapping (EIT), proximal parent artery occlusion (PAO), and flow diversion (FD) in the contemporary management of ruptured vertebral artery dissecting aneurysms (VADA) have evolved with advances in endovascular technology, but remain controversial. The aim of this retrospective cohort study is to assess the outcomes of patients with ruptured VADAs who underwent endovascular management with EIT as a first-line treatment approach. Methods: We evaluated an institutional database of patients with ruptured VADAs who were treated at Auckland City Hospital from 1998–2017. Baseline and outcomes data were analyzed to compare patients treated by EIT with those treated by PAO or FD. All cases of PAO involved occlusion of the parent VA. All cases of EIT involved occlusion of the VADA with preservation of flow through the proximal VA. Results: The study cohort was comprised of 45 ruptured VADA patients with a mean age of 47 years. EIT, PAO, and flow diversion were performed in 32 (71.1%), 12 (26.7%), and one (2.2%) case, respectively. The overall procedural complication rate was 13.3%, including procedural neurological morbidity in 4.4%. At last follow-up (mean duration 13 months), the aneurysm occlusion rate was 100%. Despite presenting with a significantly lower mean GCS (9.8 vs 13.3, p=0.029), patients treated with EIT demonstrated a significantly higher rate of neurological improvement (84.4% vs 58.3%, p=0.019), compared with those who underwent PAO. The rates of favorable outcome (modified Rankin Scale 0–2) and CSF shunt placement were not significantly different between the EIT and PAO-FD groups. Conclusion: Although individual aneurysm and anatomical characteristics must be taken into account prior to treatment, EIT remains an effective and durable first-line therapy for the majority of ruptured VADAs. Assessment of the likely origin of brainstem perforators (VA vs PICA), and of the ASA, are essential in planning potential deconstructive treatment options; flow diversion may be an option for VADAs involving the dominant VA in the absence of sufficient collateral circulation. Disclosures: D. Raper: None. D. Ding: None. J. Savage: None. J. Liu: None. J. Caldwell: None. S. Brew: None. B. McGuinness: None.